Investigating the properties of Polysilica on glass substrate for flat panel display (FPD) - Umashankar Koggri Giddappa Gowda (2008)
This project investigate the electrical properties of polysilica on glass substrate prepared by sol-gel method. The purposes include: To determine the feasibility of using polysilicates as dielectric material. To determine the effect of different amounts of acetic acid on the capacitance and dissipation factor of the capacitor.